2007
DOI: 10.1002/mds.21718
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term continuous infusion of apomorphine hydrochloride for treatment of Huntington's chorea: A double blind, randomized cross‐over trial

Abstract: We evaluated tolerability and the efficacy of continuous infusion of apomorphine hydrochloride on involuntary movements and mood disorder in Huntington's disease (HD) patients in a pilot, single center, double-blind, randomized, crossover, and controlled versus placebo study. Nine patients with a molecular diagnosis of HD were screened for response to acute apomorphine injection. Four of them, not ameliorating at the acute test, were discontinued. Five patients, responding to acute apomorphine, received contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…It was originally developed for hospital inpatients suffering from affective disorder, which explains the emphasis on melancholic and physical symptoms of depression. The HAM‐D has been used in many studies in HD to assess depressive symptoms, including clinical trials . It has been shown to correlate with the “depressed mood” item of the UHDRS ( r = 0.917) .…”
Section: Scales With a Single Behavioral Domain Assessedmentioning
confidence: 99%
“…It was originally developed for hospital inpatients suffering from affective disorder, which explains the emphasis on melancholic and physical symptoms of depression. The HAM‐D has been used in many studies in HD to assess depressive symptoms, including clinical trials . It has been shown to correlate with the “depressed mood” item of the UHDRS ( r = 0.917) .…”
Section: Scales With a Single Behavioral Domain Assessedmentioning
confidence: 99%
“…At this dose, sedation becomes a potential adverse effect. In a few short-term studies (hours), there is evidence that dopamine agonists may reduce the motor signs of HD, vaguely defined as "abnormal involuntary movements" in 2 of the studies and a reduction in the UHDRS total motor score and abnormal involuntary movement scale (AIMS) with apomorphine infusion [100][101][102]. Although the pharmacological rationale for using dopamine agonists in the treatment of chorea is not clear, presumably they act by activating the presynaptic dopamine receptors leading to decreased dopamine turnover.…”
Section: Pharmacological Treatment Optionsmentioning
confidence: 99%
“…No clinimetric data on reliability or validity of the AIMS are available in HD. The AIMS has been used in several clinical trials targeting the treatment of chorea in HD and has been shown to be sensitive to change after treatment …”
Section: Resultsmentioning
confidence: 99%